2014
DOI: 10.1016/j.amepre.2013.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Health and Economic Impact of Breast Cancer Mortality in Young Women, 1970–2008

Abstract: Background Breast cancer is the second-leading cause of cancer-related deaths among women aged <50 years. Studies on the effects of breast cancer mortality among young women are limited. Purpose To assess trends in breast cancer mortality rates among women aged 20–49 years, estimate years of potential life lost (YPLL), and the value of productivity losses due to premature mortality. Methods Age-adjusted rates and rate ratios (RRs) were calculated using 1970–2008 U.S. mortality data. Breast cancer mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 37 publications
2
37
0
1
Order By: Relevance
“…The results suggest that, in addition to the mortality impact, 33 the medical care cost of breast cancer among younger women with breast cancer is high. The results also highlight the importance of health insurance coverage for younger women to avoid potential financial hardship.…”
Section: Discussionmentioning
confidence: 98%
“…The results suggest that, in addition to the mortality impact, 33 the medical care cost of breast cancer among younger women with breast cancer is high. The results also highlight the importance of health insurance coverage for younger women to avoid potential financial hardship.…”
Section: Discussionmentioning
confidence: 98%
“…Although a recent study has reported on the economic impact associated with premature death in younger women, an update of this study may be needed, specifically for women aged 18–44 years. 7 In addition, studies on financial burden such as out-of-pocket/family income spent during medical care, transportation costs to and from medical care treatments, and child/dependent care costs, particularly for women at childbearing age are not included in this compilation of papers and are currently lacking in the literature.…”
Section: Moving Forwardmentioning
confidence: 99%
“…6 During the past four decades, incidence of breast cancer was much higher in older women (aged >50 years) and the survival rate was lower in younger women (aged <50 years). 7 This is in part because breast cancer in women aged 15–44 years (henceforth referred to as younger women) is often characterized by aggressive tumor subtypes that are less likely to be amenable to treatment at the time of diagnosis and have poorer survival outcomes. 8–11 As a result, these breast cancers could result in more devastating health outcomes and economic burden to younger women, their families, and society.…”
mentioning
confidence: 99%
“…The authors calculated the total productivity loss attributable to death from breast cancer among women younger than 50 years to be approximately $5.5 billion in 2008 alone. 7 Heightened breast health awareness among the expanded population of young women in the United States may promote genetic testing to inform screening and prevention decisions, earlier detection of disease, and improved morbidity and mortality. Because younger women are more likely to have more aggressive tumors, 5 they are also more likely to require treatments associated with the greatest toxicities and highest costs, such as chemotherapy and targeted biologic agents.…”
mentioning
confidence: 99%